Huge cystic hepatic lymphangiomain a 2-months-old infant: A case report (Indian Journal of Case Reports, 2019)
Hepatic lymphangioma is a rare benign lesion resulting from maldevelopment of the liver lymphatic vessels. It is usually associated with lymphangiomas of other viscera. Solitary lymphangioma of the liver is very rare. We report a rare case of solitary huge cystic hepatic lymphangioma in a two-months-old female infant. She presented with an abdominal mass. Imaging investigations showed a large, multiseptate cystic hepatic mass compressing the bladder but with no solid component. She had surgical resection of the hepatic mass. Histological examination revealed a cystic structure lined by epithelial cells and lymphocytes on the inner walls. The patient was last seen in the fourth-week postoperative. Subsequently, she was lost to follow up. A hepatic lymphangioma is a rare form of lymphatic malformation and its occurrence in a 2-months-old infant has never been reported.